Progress of pediatric liver transplantation: In Japan and beyond - Mureo Kasahara; Seisuke Sakamoto; Sihan Zhou; Xiuyuan Hao (Chinese Medical Journal)
Abstract. Organ transplantation, particularly pediatric liver transplantation (LT), has transformed medical practice over the past six decades, providing life-saving interventions for children with end-stage liver disease. This review demonstrated the historical milestones of pediatric organ transplantation, emphasizing Japan’s contributions, mainly through the National Center for Child Health and Development. While early transplantation efforts in the 1950s and 1960s faced significant challenges, breakthroughs in preservation methods, immunosuppressive therapies, surgical techniques, and innovations such as living donor LT in Asia have greatly improved success rates. Japan’s pediatric LT landscape is distinct, primarily due to its reliance on living donor LT, shaped by cultural and religious influences that have traditionally restricted deceased donor organ donation. This review manuscript discusses Japan’s pioneering role in expanding the indications for pediatric LT to include rare conditions such as inherited metabolic disorders and hepatoblastoma. It highlights recent innovations such as hyper-reduced lateral segment grafts, machine perfusion, and minimally invasive surgery that have further improved outcomes. International collaboration has facilitated the sharing of expertise, advancing pediatric liver transplantation practice worldwide. Despite these achievements, challenges remain, particularly in light of Japan’s declining birth rate, which threatens the sustainability of pediatric transplant services. This review emphasizes the need for centralized transplant facilities, greater awareness of brain-dead organ donation, and continued medical advances to ensure that pediatric LT remains a viable, life-saving option for future generations.